2019
DOI: 10.3390/nu11122991
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Outcomes of the Mediterranean Diet: Lessons Learned from the Predimed Randomized Controlled Trial

Abstract: The Mediterranean Diet (MD) is, culturally and historically, the nutritional pattern shared by people living in the olive-tree growing areas of the Mediterranean basin. It is of great importance for its potential preventive effect against cardiovascular diseases (CVDs). The PREvención con DIeta MEDiterránea (PREDIMED) study, a Spanish multicentre randomised controlled trial (RCT), was designed to assess the long-term effects of the MD, without any energy restriction, on the incidence of CVD in individuals at h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 72 publications
0
26
0
2
Order By: Relevance
“…Currently, the Mediterranean diet (MedDiet) is considered one of the healthiest dietary patterns based on multiple observational studies [ 8 , 9 , 10 , 11 , 12 , 13 ] ( Figure 1 ). In addition, intervention studies have evaluated the effect of MedDiets on long-term and hard clinical outcomes.…”
Section: The Mediterranean Diet In the Current Chronic Disease Conmentioning
confidence: 99%
“…Currently, the Mediterranean diet (MedDiet) is considered one of the healthiest dietary patterns based on multiple observational studies [ 8 , 9 , 10 , 11 , 12 , 13 ] ( Figure 1 ). In addition, intervention studies have evaluated the effect of MedDiets on long-term and hard clinical outcomes.…”
Section: The Mediterranean Diet In the Current Chronic Disease Conmentioning
confidence: 99%
“…Interestingly, it was found that change in the food supply in the Mediterranean area, especially more readily available mass-produced food from the long supply chain (opposite from the local food markets) was associated with MetS [18]. These trends are very misfortunate and represent a double missed opportunity, because Mediterranean diet was shown to have the capacity for preventing the development of metabolic syndrome, as well as the ability to reverse it in people with or without type 2 diabetes [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…As it is recently emerging, instead, the importance of the so-called "positive food/nutrients," whose diet reduction or absence plays an equally crucial role in increasing cardiovascular risk [15,91]. Coherently, diets based on foods particularly rich in antioxidants, phytochemicals, fiber, vitamins, monounsaturated fatty acids, and PUFAs, such as Mediterranean diet (MD) and vegetarian diet, are recognized worldwide as protective against CVD and its risk factors [8][9][10][11][12][13][14][15]. Also, in this context, it has been recognized a sex-related difference in individual responses to specific dietary habits (e.g., adherence to MD), with men displaying more favorable specific cardiometabolic changes, with respect to premenopausal women [92][93][94][95].…”
Section: Intervention Studiesmentioning
confidence: 99%
“…Among biological risk factors, platelets are emerging as new players, since increased platelet aggregation is a major determinant for heart attacks, stroke, and thrombosis: indeed, activated platelets are major components of thrombi occluding arteries and play a role in plaque formation within blood vessels during atherogenesis [7]. As a consequence, either antiplatelet therapy or other interventional strategies (such as those to promote consumption of foods rich in antioxidant and phytochemical compounds, fiber, and monoand polyunsaturated fatty acids (PUFA)) are becoming increasingly relevant for preventing and treating vascular events in high-risk patients [8][9][10][11][12][13][14][15][16]. Accidentally, also in this context, a sex and gender disparity can be identified, in terms of aggregation response capacity and susceptibility to platelet aggregation inhibitors [17][18][19].…”
Section: Introductionmentioning
confidence: 99%